Controlling a scattered field output of light passing through turbid medium using an improved ant colony optimization algorithm. (September 2021) - Yang, Zuogang; Fang, Longjie; Zhang, Xicheng; Zuo, Haoyi
Highlights: A novel phase optimization approach to focus light through scattering media is proposed. This approach aims to improve the converging speed and susceptibility. The mechanism relies on constructive interference of all phase modulated elements. Abstract: An improved ant colony optimization algorithm has been developed in the present study to control an output scattered light field after an incident beam of light passes through a turbid medium. In this newly developed algorithm, the search rules and pheromone release rules of the basic ant colony optimization algorithm were modified which led to an improved search ability of the algorithm. Through reasonable designing of the cost function, the improved ant colony optimization algorithm can shape a scattered light field through turbid medium to predetermined shape. Furthermore, simulations and experiments showed that the improved ant colony optimization algorithm offers many advantages, such as good optimization effect, rapid convergence and strong anti-interference ability.